Lytic and Chemotactic Features of the Plaque-Forming Bacterium KD531 on Phaeodactylum tricornutum - Chen, Zhangran; Zheng, Wei; Yang, Luxi; Boughner, Lisa A.; Tian, Yun; Zheng, Tianling; Xu, Hong (Frontiers in Microbiology, 2017)
Phaeodactylum tricornutum is a dominant bloom forming species and potential biofuel feedstock. To control P. tricornutum bloom or to release lipids from P. tricornutum, we previously screened and identified the lytic bacterium Labrenzia sp. KD531 towards P. tricornutum. In the present study, we evaluated the lytic activity of Labrenzia sp. KD531 on microalgae and investigated its lytic mechanism. The results indicated that the lytic activity of KD531 was temperature- and pH-dependent, but light-independent. In addition to P. tricornutum, KD531 also showed lytic activity against other algal species, especially green algae. A quantitative analysis of algal cellular protein, carbohydrate and lipid content together with measurements of dry weight after exposure to bacteria-infected algal lysate indicated that the bacterium KD531 influenced the algal biomass by disrupting the algal cells. Both chemotactic analysis and microscopic observations of subsamples from different regions of formed plaques showed that KD531 could move towards and then directly contact algal cells. Direct contact between P. tricornutum and KD531 cells was essential for the lytic process.